Dye-sensitized TiO2 nanotube membranes act as a visible-light switchable diffusion gate. Issue 12 (11th November 2019) - Hwang, Imgon; Riboni, Francesca; Gongadze, Ekaterina; Iglič, Aleš; Yoo, JeongEun; So, Seulgi; Mazare, Anca; Schmuki, Patrik
Abstract : Herein, anodic TiO2 nanotube membranes, after sensitization with a Ru(ii )-based dye, exhibit visible-light switching properties for flow-through the nanotube channels and can be used as an optically addressable flow-through gate in nanofluidics. Abstract : Here we report that both-end open anodic TiO2 nanotube membranes, after sensitization with a Ru(ii )-based dye, exhibit visible-light switching properties for flow-through the nanotube channels. Under illumination, the gate is in an open state providing ∼four-times faster permeation of small molecules through the membrane compared to a dark state. Switching is reversible with no apparent dye degradation being observed. Gating is possible not only of permeating dye molecules but also of nanoprobes such as polystyrene nanospheres. Supported by quantitative modelling, we attribute the switching mechanism to light-induced changes of the charge distribution at the dye/TiO2 interface which in turn alters the hydrodynamics within the anodic tube membranes. This demonstrates that these simple dye-sensitized nanotube membranes can be used as an optically addressable flow-through gate in nanofluidics.